Analysis of the interaction of Hsp90 with the extracellular matrix protein fibronectin (FN) - Hunter, Morgan Campbell (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
Mounting evidence suggests that Hsp90 is present and functionally active in the extracellular space. The biological function of extracellular Hsp90 (eHsp90) remains relatively uncharacterized compared to that of intracellular Hsp90. eHsp90 has been shown to interact with a finite number of extracellular proteins, however, despite the identification of eHsp90 interacting proteins, the function of eHsp90 in these complexes is unknown. Several reports suggest a role for eHsp90Î± in cell migration and invasion. Reported targets for eHsp90 stimulated cell migration include MMPs, LRP-1, tyrosine kinase receptors and possible others unidentified. Limited studies report a role for eHsp90Î². Recently, Hsp90Î± and Hsp90Î² were isolated in a complex containing fibronectin (FN) on the surface of MDA-MB-231 breast cancer cells. Herein, we report direct binding of Hsp90Î± and Hsp90Î² to FN using a solid phase binding assay and surface plasmon resonance (SPR) spectroscopy. SPR spectroscopy showed that Hsp90Î² bound the 70 kDa amino-terminal fragment of FN (FN70), but that binding of FN to Hsp90Î² was not limited to FN70. Confocal microscopy showed regions of colocalization of Hsp90 with extracellular FN matrix fibrils in Hs578T breast cancer cell lines. Treatment of Hs578T breast cancer cells with novobiocin (an Hsp90 inhibitor) and an LRP-1 blocking antibody resulted in a loss of FN matrix and FN endocytosis (novobiocin treated). Addition of exogenous Hsp90Î² was able to recover such effect after both treatments. FN was shown to colocalize with intracellular LRP-1 in novobiocin treated Hs578T cells. Immunoprecipitation of an LRP-1 containing complex showed the presence of Hsp90 and 70 and 120+ kDa FN fragments. Treatment of Hs578T cells with novobiocin increased the level of FN120+ bound in LRP-1 immunoprecipitate. Exogenous Hsp90Î² decreased the level of low and high molecular weight FN fragments in a complex with LRP-1, despite the fact that higher levels of lower molecular weight FN fragments were detected in this cell lysate compared to the other treatments. We report FN as a novel interacting protein of eHsp90. Taken together, we provide evidence for a direct role of eHsp90Î² in FN matrix remodeling. We suggest that Hsp90 plays a direct role in FN matrix dynamics through interaction with FN and LRP-1. The identification of FN as a novel interacting protein of eHsp90 suggests a role for Hsp90 in FN matrix remodeling, which is important for a number of fundamental cellular processes including cell migration and metastasis.
Keywords: Heat shock proteins; Fibronectins; Extracellular matrix proteins; Breast -- Cancer